The Tolerability and Degradation Rate of Amoxicillin Alone and with Clavulanic Acid in the Acidic and Alkaline Medium - Abbas Razzaq Abed (Journal of Global Pharma Technology, 2016)
This study deal with the effects of various pH values (1-14) on the stability of Amoxicillin alone and with Clavulanic acid. The degradation rate of Amoxicillin alone and with Clavulanic acid was determined by using Bacillus thuringiensis as indicator to act of drug used in this study. Amoxicillin alone and with Clavulanic acid was high stability at an acidic pH, while increasing the pH value led to decrease its stability at the statistical level (P value < 0.05). Maximum stability of Amoxicillin alone and with Clavulanic acid was experienced at pH values (4, 5,6,7,8 and 9), While their degeneration rate was significantly higher at acidic medium (pH=1) and alkaline pH medium (pH= 11, 12, 13 and 14) at p-value < 0.05. Therefore, the Amoxicillin alone and with Clavulanic acid is best given to humans and animals in pH value from 4-9.Keywords: Tolerability, Degradation, Amoxicillin, Clavulanic, acid, Alkaline, Medium.